Why Ethics Needs Metaphysics? - Noreikaitė, Aistė (Problemos, 2019)
The aim of this paper is to show that Ronald Dworkin’s objective to isolate ethics from metaphysics is not sufficiently grounded, and a certain metaphysics is inherent even in his own position of autonomous ethics. While opposing those thinkers who seek to ground ethics by finding an external – neutral and non-evaluative – ground, Dworkin identifies this externality to ethics with metaphysics and aims to show its fallibility. However, such a conception of metaphysics seems to be too narrow and one-sided and leads his own position into contradictions. This paper aims to demonstrate these contradictions and to argue that even the position that is inner to ethics and stems from a first-person agent’s perspective can only be developed while considering such metaphysical ideas as freedom, dignity, person.
Keywords: ethics; metaphysics; Ronald Dworkin; ethical subject